Bioethics: The Bridge Between Clinical Practice and Medical Education - Pina, João (Journal of the Portuguese Society of Anesthesiology, 2019)
The author draws attention to the drift that medical art is suffering by reference to its vocational origins, seeking to direct or look into what, explicitly or camouflaged, deliberately or subliminally, seems to be being pursued by the primacy of materialism and technicalism. Under the guise of a kind medicine, by definition, besetting with ambition and arrogance, the corruption of medical art in its ethical and humanistic dimension is eroding the education and loyalty of the new doctors. In an attempt to cover under a theme all the factors that deserve a signal in the path of medical education, the concept of hodegetics is recovered. Finally, the author grants emancipation and autonomy to the so-called medical burnout, as cause and consequence of a medicine that is weakened, a victim of the man in general and of the doctor himself, who can deeply hurt clinical practice and, therefore, medical education. The reflection here presented seeks inspiration from metaphors, philosophers and cultures prior to the phenomenon of globalization, whose doctrines and lines of social action defend the universality of the value of full human life, seeking in wisdom and virtue the way to happiness and final well-being, something similar to eudaimonia, central concept in Aristotle's ethics and philosophy. The Good where the responsible virtue of the master intertwines with the hope of the apprentice and the altruistic solidarity of the patient himself. It is in this ambitious ethical embrace that the author intends to bridge the gap between clinical practice and medical teaching.